Alterations of brain structural MRI are associated with outcome of surgical treatment in trigeminal neuralgia. (24th September 2021) - Albano, Luigi; Agosta, Federica; Basaia, Silvia; Castellano, Antonella; Messina, Roberta; Parisi, Veronica; Barzaghi, Lina Raffaella; Falini, Andrea; Mortini, Pietro; Filippi, Massimo
Abstract: Background and purpose: To assess magnetic resonance imaging (MRI) alterations occurring in patients with trigeminal neuralgia (TN) and to explore the predictive ability of MRI for initial surgical outcome and long‐term pain relief/recurrence after Gamma Knife radiosurgery (GKS). Methods: Thirty patients with idiopathic or classic TN, who underwent GKS and were followed for at least 24 months, were retrospectively included. Pre‐treatment structural MRI and pre‐ and serial, postoperative clinical features were investigated. Fifteen age‐ and sex‐matched healthy controls were also enrolled. Cortical thickness and gray matter (GM) volumes were assessed in TN patients relative to controls, as well as between patient subgroups according to treatment outcomes (initial responders/non‐responders, patients with pain recurrence/long‐lasting pain relief at the last follow‐up). Clinical and MRI predictors of treatment outcomes were explored. Results: Cortical thinning of temporal, prefrontal, cingulate, somatosensory and occipital areas bilaterally was found in TN patients relative to controls. No cortical thickness and GM volume differences were observed when TN initial responders and non‐responders were compared. Patients who experienced TN recurrence after initial pain relief were characterized by thicker parahippocampal and temporal cortices bilaterally and greater volume of right amygdala and hippocampus compared to patients with long‐lasting pain relief. In TN patients, disease duration and baseline cortical thinning of right parahippocampal, left fusiform and middle temporal cortices were associated with poor outcome after GKS at the last follow‐up ( R 2 =0.57, p <0.001). Conclusion: The study provides novel insights into structural brain alterations of TN patients, which might contribute to disease development and pain maintenance. Abstract : This study provides novel insights into structural brain alterations of TN patients, which might contribute to disease development and pain maintenance.